DRAWING A HUMAN SKULL IN A PEN DRAWING (nose, ears, eyes, lips) - Khasanov Kholboy Khasanovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article provides information on how to draw a pencil drawing of a human skull. In this process, special attention is paid to the study in parts.